Carrying Capacity Assessment of Tanjung Putus Lake for Extensive Fishing Based on Chlorophyll-a - Buala Ziduhu Laia; Asmika Harnalin Simarmata; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The carrying capacity is defined as the ability of aquatic environment to support the life of organism in that area. A study aimed to assess the aquatic carrying capacity for extensive fishing in the Tanjung Putus Lake, Buluh China Village, Kampar District, Riau. The carrying capacity was determined based on primary productivity using chlorophyll-a value, which is indicating the existence of phosphate in waters.This research was conducted March, 2018.There were 3 stations namely station 1 (inlet area), station 2 (in the middle of lake) and station 3 (outlet area). In each stations, there were 2 sampling sites, in the surface and in the middle of water column. Sampling was done three times, once a week. Water quality parameters measured weretransparency, temperature, pH, dissolved oxygen, phosphate and nitrate concentration. Results shown that chlorophyll-a: 6.98-7.52 µg/L, transparency: 85.17-96.5 cm, temperature: 30.2-31.8 oC, pH: 5, dissolved oxygen: 4.82-         6 mg/L, phosphate: 0.05-0.09 mg/L and nitrate: 0.05-0.06 mg/L. The concentration of chlorophyll-a indicates that the carrying capacity of the Tanjung Putus Lake for extensive fishing was 1,74 tons/year. Keyword: Oxbow lake, Extensive fishing, Phytoplankton, Water quality